Biografia młodego Karola Wojtyły w rosyjskiej i rosyjskojęzycznej prasie = Early Karol Wojtyla`s biography in Russian and Russian-speaking press - Gorzelana, Joanna; Seul, Anastazja (1961- ) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The authors intend to show how the biographical elements of Karol Wojtyla are presented in Russian and Russian-speaking magazines. They analysed the occasional newspaper articles available on the internet about the future Pope`s youth. The authors highlighted the following topics: family background, the course of the education, people and situations during the occupation that led him in the decision of choosing his future way of life. Based on studied texts the authors extrapolate that the choice of biographic information depends on the outline of the periodic. Moreover, in many texts can be seen lack of objectivity and lack of journalist`s diligence as well as the presence of misrepresentation of the young Wojtyla portrayal. In addition to their illocutionary function, the materials studied also have a perlocutionary function, conveying an ideology that belittles the role of the Catholic religion in the world.
Keywords: Jan Paweł II, papież (1929-2005); biografia; czasopismo rosyjskojęzyczne; selektywność; religia; okupacja; biography; Russian-language press; Russian press; selectiveness; religion; occupation